Synodality in a Communion-Church - Lawler, Michael G.; Salzman, Todd A. (Asian Horizons, 2020)
The Second Vatican Council mandated a synod of Bishops to “bear testimony to the participation of all Bishops in hierarchical communion in the care of the universal Church.” Synods, gatherings of Bishops to discuss specific questions arising in the Church, have been frequent since the Council. One of the major theological contributions of the Council was the renewal of the notion of the Church as a communion of believers, laity and clerics together. Basing ourselves on this notion of Church as a communion of believers, in this essay we propose synods of all the People of God to discuss questions important to the Church and to bear testimony to the participation of all believers in the mission and care of the communion-Church. We base our proposal on not only a communion model of Church, but also Catholic teaching on the authority and inviolability of conscience and the concept of synodality that so characterizes the papacy of Pope Francis.